BOVINE EMBRYO PRODUCTION BY IN VITRO FERTILIZATION USING CRYOPRESERVED GAMETES - Huyền, Nguyễn Thị Thương (Vietnam Journal of Biotechnology, 2011)
This  research  aimed  at  bovine  embryo  production,  using  cryopreserved  mature  bovine  oocytes  by vitrification,  and  cryopreserved  sperms.  The  cumulus-oocyte  complexes  (COCs)  were  obtained  from  cow ovaries  by  aspiration.  COCs  with  three  or  more  layers  of  cumulus  cells  and  homogeneous  cjftoplasm  were selected  to  be  cultured  in  Ci  medium  (TCM-199,  10% FBS,  10 ng  EGF,  0.2  mM  Na  pyruvate,  50  (ig/ml gentamicin)  under  the  condition  at  38.5°C  with  humidified  atmosphere  of  5%  CO2 in  au.  After  22  -  24 h incubation,  matured  oocytes   were  cryopreserved  by  vitrification  method  in  sfraws  in two  steps:  (i)  oocytes were first equilibrated in the VS,  solution (TCM-199 +  10% FBS +  10% DMSO +  10% EG) for 45 seconds; (ii) The oocytes were then fransfenred in the VS2 solution (TCM-199 + 10% FBS -I- 20% DMSO + 20% EG + 1 M sucrose) for 25 seconds. Each sfraws  were loaded with five to seven oocytes. Sfraws were plunged directly into hquid nifrogen  within 25 - 40 seconds at the begirming  of the exposure to  second  step. After  storage in hquid nitrogen, thrawing  was performed  by  exposing  the  sfraw  to air for  5 seconds, and plunged  into warm water  (37°C) for  10 seconds, and then fransfered were  oocytes  into  clean  dish  (35); Oocytes were directly expelled into RD, medium (TCM-199  -1- 10% FBS  -1- 0.25 M sucrose)  1.5 minutes, RD2 medium (TCM-199 -1-10% FBS + 0.15  M sucrose)  1.5  minutes and RD3 (TCM-199 +  10% FBS) medium  5 minutes; This  oocytes were franferred to  Cj  medium  and holding   for  3 minutes. The thrawing  was performed  in  a room  at 25°C. After 22 - 24 h incubation, the number of oocytes observed with Metaphase 11 stage were 2658/3276 (81.19 ± 2.75%); morphological  intact recovered rate was 76.08%. After 22 - 24 h incubation with sperm, insemination rate (two-cell embryo) was 11.67% and 46/144 embryos developed into blastocyst stage